PENGARUH CELEBRITY ENDORSER DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE THE ORIGINOTE PADA APLIKASI TIKTOK (Studi kasus pada Masyarakat Kec Dukuhturi) - Fatoni, Umi Fadilah; Rukminto, Reny Melyana; Ainunnisa, Ulfi (Medikonis, 2025)
This research aims to determine the influence of Celebrity and Electronic Word Of Mouth on purchasing decisions for The Originote products, partially and simultaneously. The research method used in this research is research using a quantitative approach to The Originote skincare. The population in this study were consumers of The Originote skincare products and the respondents in this study were 50. The data collection method used a questionnaire. Data analysis techniques in this research include Validity Test, Reliability, Normality, Multiple Linear Regression, and Hypothesis Testing. The research results show that Celebrity Endorsers have an influence on Purchasing Decisions. This is proven by the results of testing the Celebrity Endorser hypothesis Tcount > Ttable (8.676 > 2.01174) with a significance level of 0.000. Electronic Word Of Mouth shows Tcount > Ttable (4.991 > 2.01174) with a significance level of 0.000. And simultaneously Celebrity Endorser and Electronic Word Of Mouth influence the decision to purchase The Originote product with a value of Fcount > Ftable (93.076 > 3.20).